Gravitational lensing of the CMB by galaxy clusters - Maturi, Matteo; Bartelmann, Matthias; Meneghetti, Massimo (Arxiv, 2013)
We adapt a non-linear filter proposed by Hu 2001 for detecting lensing of the CMB by large-scale structures to recover surface-density profiles of galaxy clusters from their localised, weak gravitational lensing effect on CMB fields. Shifting the band-pass of the filter to smaller scales, and normalising it such as to reproduce the convergence rather than the deflection angle, we find that the mean density profile of a sample of 100 clusters can be recovered to better than 10% from well within the scale radius to almost the virial radius. The kinetic Sunyaev-Zel'dovich effect is shown to be a negligible source of error. We test the filter applying it to data simulated using the characteristics of the Atacama Cosmology Telescope (ACT), showing that it will be possible to recover mean cluster profiles outside a radius of 1' corresponding to ACT's angular resolution.